Pacific Walrus Behavior Data and Associated Chukchi Sea Ice Observations and Projections for use with Bioenergetics Models to Forecast Walrus Body Condition ... - Anthony S Fischbach; William S Beatty; Chadwick V Jay; Mark S. Udevitz (U.S. Geological Survey, 2017)
This data release includes three datasets used to develop forecasts of autumn body condition for adult female Pacific walruses in the Chukchi Sea during mid and late century time periods. (1) The activity dataset contains daily telemetry records for 218 adult female walruses tracked for periods of 7 to 104 days during 2008-2014, in the Chukchi Sea. Records include the number of hours the walrus was in the water, number of hours the walrus was foraging, study area region where the walrus was located, depths of the foraging locations, and the proportion of the region covered by sea ice. (2) The movement dataset contains telemetry records for 94 of these walruses, giving the dates they moved from one region to another, and the date of the beginning of minimum ice period for that year. (3) The projected-ice dataset contains daily projections of ice conditions in the study area regions derived from 7 general circulation models of future ice availability for mid-century (2045-2054) and late-century (2090-2099) ...